The Effectiveness Of Providing Vulanic Ash (Tuff Vulcan) And Dolomite As Amelioran Materials On The Growth Of Immature Liberica Coffee Plants In Peat Land Of Mekar Jaya Village - Armando, Y. G.; Maryani, Anis Tatik; Syarif, M. (LPPM Universitas Jambi, 2020)
Liberika coffee is one type of coffee that is widely cultivated by people in wetland areas (peat) precisely in Betara District, Tanjung Jabung Barat Regency. In recent years, this district has become a development center and provider of Liberika coffee seeds for coffee plantation farmers from various regions such as Palembang, Kalimantan and Riau. Liberika coffee is a type of coffee that is able to adapt and produce quite well in peatlands with areca nut as a cover crop. The productivity of coffee in this area is still low at an average of 715 / kg when compared to the potential yield of Liberika coffee which can reach 950 kg / ha. Increasing production and productivity can be done through intensification and extensification. One of the efforts to improve the physical and chemical properties of peat soils so as to increase the growth and production of coffee plants is the use of ameliorants (soil enhancers). This study aims to develop a technology for using ameliorant to improve the chemical properties of peat soil. Specifically, through this study, the dosage combination of vulcan tuff ash and dolomite can be identified. which can substitute the use of artificial fertilizers (inorganic) so that it can increase the growth and production of immature liberica coffee plants on peatlands. especially the coffee plantation of farmers in the village of mekar jaya, betara district, tanjung jabung west district. From the results of this study it can be concluded that the treatment of volcanic ash and dolomite did not show significant differences in plant height parameters and, stem diameter. but it gives a real difference to the growth of live area, the number of flowers per bunch and the number of flowers in each bunch. treatment of volcanic ash 500 / gr / tree and dolomite 500 / gr / tree and a combination of volcanic ash 250 / gr / tree + dolomite 250 / gr / tree after 7 weeks of application can significantly spur on the initiation of flowering an average of 7 bunches of branch flowers if compare with control (no treatment). Likewise, observations 8 weeks after application showed the same thing, there was an increase in the number of flowers formed an average of 11 flower clumps branching. From the results of this study, it can be concluded that the provision of ameliorant from vulcan tuff ash and dolomite can improve the chemical properties of peat soil so as to increase nutrient availability for growth and production of the Liberika coffee plant. From the results of this study, it can also be suggested that the use of volcanic ash and dolomite at a dose of 250-500 gr / tree to accelerate the productive phase of immature liberica coffee plants (young plants) in peatlands.